Continuous Productive Urban Landscape - Rawaa Fawzi Naom Abbawi; Fatima Fouad Yaseen (Iraqi Journal of Architecture and Planning, 2017)
The research had taken the concept of Continuous Productive Urban Landscape that appeared within the sustainable trends in the city, provides the opportunity to address the problems of lack in city open space, strengthen the relationship between the built environment and nature, access to multi-functional landscape.Therefore, it request the need of research in this concept and determine its properties, so the research problem appeared, in the need of a theoretical framework for the properties of Continuous Productive Urban landscape, To help designers having its benefits in the design process.Thus, the aim of this paper is to construct an inclusive theoretical framework of continuous productive urban landscape properties.In order to solve the research problem, a previous literature review of the origin of the concept, has reached to the most important design properties of the Continuous Productive Urban landscape and determine the vocabularies and indicators relevant to it.Then had been measured the validation values of the properties and its vocabularies and indicators, through analytic study for three projects had applied Continuous Productive Urban landscape within cities.The results shown the variant in verification of these properties, coherence property emerged as a main design property, followed by integration then diversity.Finally, had reached to a theoretical model for the properties of the Continuous Productive Urban Landscape in the city.